Ophthalmomyiasis in a preterm neonate resulting in blindness: A case report from Botswana - Nakstad, Britt; Zandile, Yeni; Gaebolae, Kesiilwe; Banda, Francis Msume; Dinotshe, Tebo; Imran, Fizzah; Gezmu, Alemayehu Mekonnen (Frontiers in Pediatrics, 2022)
Myiasis is an infestation of human tissue by insect larvae. While rare, healthcare-associated myiasis has been reported from immobilized patients in resource-limited healthcare facilities in warm climates without adequate vector-control measures. We describe a case of ophthalmomyiasis in a hospitalized neonate in Botswana that resulted in vision loss. The neonate, who was initially hospitalized due complications of prematurity, received phototherapy for jaundice and, to avoid phototherapy-related retinopathy, the neonate’s eyes were covered using cotton gauze and adhesive tapes that potentially damaged the skin as commercially available eye-covering was not in stock. Therefore eye-covering was not changed and when the eye covering was removed almost 3 days after placement, insect larvae were noted in the patient’s eyes and nose. Ophthalmologic evaluation revealed perforated corneal ulcer and uveal prolapse in the right eye resulting in complete blindness, and corneal scarring of the left eye. The patient’s clinical course was further complicated by an Enterobacter species bloodstream infection. This case highlights the importance of vector-control as a vital patient safety measure for neonatal units in warm climates. Flies had been observed in the room and mitigation measures included reducing fly populations through traps, screens, and removal of standing water and leftover food. Every mother and staff were sanitizing hands when entering the room and gowns were used. This case also reinforces the importance to conduct vigilant monitoring of patients, especially neonates with eyes covered during phototherapy.